Second Rome through the Εyes of the Τhird One. The Evolution of the Ιmage of Byzantium in the Russian Social Consciousness (Forum Theologicum Sardicense, 2025)
The article examines the impact of the image of Byzantium and the Byzantine political and religious model on Russia. It explores how this model has influenced Russia and the Russian mindset, investigating the depth of its roots and how historical truth is often overshadowed by politically convenient falsehoods. The article demythologizes the historical concept of the ‘Third Rome’ and offers strong criticism of both Russian politicians and scholars who increasingly manipulate the idea and significance of this term.
Keywords: Byzantine Political System; Russian Messianism; Second and Third Rome; Russian Imperialism